Allergy clinics in times of the SARS‐CoV‐2 pandemic: an integrated model. Issue 1 (18th June 2020) - Malipiero, Giacomo; Heffler, Enrico; Pelaia, Corrado; Puggioni, Francesca; Racca, Francesca; Ferri, Sebastian; Spinello, Lina; Merigo, Morena; Lamacchia, Donatella; Cataldo, Giuseppe; Sansonna, Melissa; Canonica, Giorgio Walter; et al.
Abstract: Background: Almost the entire World is experiencing the Coronavirus‐Disease‐2019 (COVID‐19) pandemic, responsible, at the end of May 2020, of more than five million people infected worldwide and about 350, 000 deaths. In this context, a deep reorganization of allergy clinics, in order to ensure proper diagnosis and care despite of social distancing measures expose, is needed. Main text: The reorganization of allergy clinics should include programmed checks for severe and poorly controlled patients, application of digital medicine service for mild‐to‐moderate disease in well‐controlled ones, postponement of non urgent diagnostic work‐ups and domiciliation of therapies, whenever possible. As far as therapies, allergen immunotherapy (AIT) should not be stopped and sublingual immunotherapy (SLIT) fits perfectly for this purpose, since a drug home‐delivery service can be activated for the entire pandemic duration. Moreover, biologic agents for severe asthma, chronic spontaneous urticaria and atopic dermatitis should be particularly encouraged to achieve best control possible of severe disease in times of COVID‐19 and, whenever possible, home‐delivery and self‐administration should be the preferred choice. Conclusion: During COVID‐19 pandemic, allergists have the responsibility of balancing individual patients' needs with public health issues, and innovative tools, such as telemedicine and digital medicine services, can be helpful to reduce the risk of viral spreading while delivering up‐to‐date personalized care.